Fuel cells as effective means of chemical power source - Войтко, І.І. (Proceedings of National Aviation University (archive), 2004)
The sources of literature related to fuel cells application had been analyzed. Conclusion had been made that they can be used as independent power supplies (sources), particularly in the field of aerospace. Although the most progressive way of their development as expected created hybrid energy systems.